Oaks as a Feed Ingredient for Ruminants: A Review - Hoger Hidayet; Jalal Alkass; Kamal Mustafa (Mesopotamia Journal of Agriculture)
The influences of oak inclusion into the diet of ruminants on performance, feed digestibility, milk production and blood metabolites are reviewed herein. Oak as an alternative and available feed are being utilized in many parts of the world, especially in areas suffering from a shortage of feed ingredients. It is evident that different oak species have different impacts on various animal species. Oak fed at low levels in the diet may not affect digestibility, but when they are fed at high level may lead to lessen the digestibility of dry matter. Adding oak products may improve the daily milk yield of goats. Feeding oak acorns and leaves to growing goat kids might not been accompanied by significant improvement in daily weight gain and feed conversion ratio, while when feeding adult sheep on high level of dietary oak, it may result in lowered daily weight gain. Different oak species produce different amounts of tannins, which after ingestion by animals, act to form complexes with the proteins of diet, this may lead to lower digestibility of nutrients or may beneficially affect to positive flow of amino acids into abomasum and small intestine by reducing the protein degradability in the rumen. Thus, the extent of the impact of dietary oak on ruminants’ performance depends on the species of both animals and oak, and the level of oak being used in the diet.